Boa postura analítica e Gevrey da “boa” equação de Boussinesq - Figueira, Renata de Oliveira (Universidade Federal de São Carlos, 2021)
In both the line and the circle, we shall to prove that the Cauchy problem for the ``good'' Boussinesq equation is locally well-posed in a class of Gevrey functions, which includes a class of analytic functions that can be extended holomorphically in a symmetric strip of the complex plane around the x-axis. Additionally, information about the regularity of the solution in the time variable shall be provided.
Analytic and Gevrey well-posedness of the "good" Boussinesq equation
Keywords: Boussinesq; Good Boussinesq; Time regularity; Gevrey well posedness; Well posedness; Bourgain Spaces; Well-posedness; CIENCIAS EXATAS E DA TERRA::MATEMATICA